Prohibition Excessive in Worship: Analysis of Hadith from Muslim History in the Shahih Book No. 1159 - Athiyatul Maziyah; Abdul Karim Amrullah; Viki Junianto; Farhan Ali Ishaqi (Medina-te : Jurnal Studi Islam, 2024)
This study discusses and analyzes a hadith from Sahih Muslim, numbered 1159, in his authentic collection. This hadith addresses the Prophet's prohibition directed toward a companion who continuously engaged in worship to the extent of neglecting his family’s rights and the rights of others. The aim of this research is to establish the hadith's level of authenticity ("Sahih")and to explore its meanings. Although this hadith is categorized under fasting, related hadiths are not limited to fasting; they also cover topics such as night prayers, marriage, the prohibition of castration for men, the fasting of Prophet Dawud, and other acts of worship. The analysis of this hadith involves several stages: conducting comprehensive Takhrij Hadith (verification of sources), Jarh wa Ta'dil (critique and assessment of narrators), I'tibar Sanad (evaluation of the chain of transmission), and Naqd Al-Matan (textual criticism). Through these stages, the authenticity and classification of the hadith can be determined. The understanding of the hadith is further examined using hadith commentaries (syarh) and contemporary scholars’ methodologies, which serve as resources in this research. Data collection is conducted using the Library Research method, compiling classical texts, journals, and scholarly books as references for this study. The research concludes that the hadith narrated by Muslim, number 1159, regarding the prohibition of excessive worship, reaches the classification of "Sahih Lidzatihi" (authentic in itself). The understanding derived from this hadith is that the prohibition against excessive worship is not absolute; as long as it does not exceed the limits of Shari’a and does not neglect the rights of others, the acts of worship performed are considered good deeds that are highly encouraged by Islamic teachings.